Effectiveness of Clitoria ternatea L. Nanoherbal on Blood Glucose and Malondialdehyde Levels of Hyperglycemic Rats - Cahya Buana; Wulan Christijanti; Ari Yuniastuti (Universitas Labuhanbatu, 2026)
Background: Hyperglycemia induces excessive production of reactive oxygen species (ROS), leading to oxidative stress and lipid peroxidation characterized by increased malondialdehyde (MDA) levels. This study evaluated the effectiveness of butterfly pea flower nanoherbal formulated as alginate-based nanoparticles using the ionic gelation method in reducing blood glucose and MDA levels in hyperglycemic rats. Methodology: 25 male Wistar rats (Rattus norvegicus) were divided into five groups: normal control (NC), metformin control (MC), and three nanoherbal treatment groups (NT1, NT2, and NT3) receiving doses of 12.5, 25, and 50 mg/kg body weight (BW), respectively. Hyperglycemia was induced by a single intraperitoneal injection of alloxan monohydrate (125 mg/kg BW). Blood glucose was measured on days 1, 14, and 28, while MDA levels were analyzed on day 28 using the TBARS method. The analysis of blood glucose levels was conducted using a Repeated Measures Two-Way ANOVA followed by a Bonferroni post hoc test, while MDA data were evaluated through a One-Way ANOVA with Duncan’s multiple range test (p < 0.05). Findings: A significant, dose-dependent reduction in blood glucose levels was observed following nanoherbal treatment. The NT3 group (50 mg/kg BW) showed the greatest reduction, with mean glucose decreasing from 471.4 ± 142.00 mg/dL on day 1 to 146.4 ± 68.58 mg/dL on day 28. MDA levels also differed significantly, with NT3 showing 2.84 ± 0.19 nmol/mL, indicating lower oxidative stress. Contributions: These findings indicate that alginate-based butterfly pea nanoherbal can reduce blood glucose and MDA levels in hyperglycemic rats, suggesting its potential role in improving glycemic control and reducing oxidative stress under hyperglycemic conditions